Development and Preliminary Application of a Triplex Real-Time Quantitative PCR Assay for the Simultaneous Detection of Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum - Zhang, Yaoguang; Chen, Jian; Pan, Hao; Ma, Xiaojiang; Jiang, Li; Zhu, Qian; Wu, Huanyu; Wang, Zhenyu (Frontiers in Microbiology, 2022)
Objectives: In this study, we aimed to develop a triplex real-time quantitative PCR (qPCR) for the simultaneous differential detection of Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum. Methods: Specific primers and TaqMan probes were designed for the 16S-like SSU rRNA sequence of E. histolytica, the gdh sequence of G. lamblia, and the 18srRNA sequence of C. parvum. A triplex qPCR assay was developed based on single-duplicate experiments to evaluate its sensitivity, specificity, stability, and reproducibility. Additionally, 163 fecal samples from patients with diarrhea who tested positive for copro-antigen were tested to verify the practicality of the assay. Results: The triplex qPCR assay could specifically detect E. histolytica, G. lamblia, and C. parvum without cross-reactivity amongst the target-specific TaqMan probes of these three intestinal protozoan parasites and did not produce amplification curves for any other non-target species, and had good specificity. Amplification of serial dilutions showed that the triplex qPCR detected as little as 500 copies/μL of standard plasmid DNA. The standard curve displayed good linearity between 5×102 and 5×108 copies/μL; qPCR assays were performed with an efficiency of more than 94% and R2 values were greater than 0.99. The triplex qPCR assay had good repeatability with intra- and inter-assay coefficients of variation less than 1.92%. Among the 163 fecal samples, four samples were confirmed to be positive for C. parvum using the triplex qPCR assay. Conclusions: The triplex qPCR established in this study not only provides a rapid, sensitive, specific tool for the simultaneous detection of E. histolytica, G. lamblia, and C. parvum, but also has good practical application value.